2020
DOI: 10.1007/s12298-020-00768-4
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling salinity stress responses in ancestral and neglected wheat species at early growth stage: A baseline for utilization in future wheat improvement programs

Abstract: In this study, we analyzed the behavior of several neglected, ancestral, and domesticated wheat genotypes, including Ae. triuncialis, Ae. neglecta, Ae. caudata, Ae. umbellulata, Ae. tauschii, Ae. speltoides, T. boeoticum, T. urartu, T. durum, and T. aestivum under control and salinity stress to assess the mechanisms involved in salinity tolerance. Physiological and biochemical traits including root/shoot biomasses, root/shoot ion concentrations, activity of antioxidant enzymes APX, SOD, and GXP, and the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 56 publications
(60 reference statements)
6
24
0
Order By: Relevance
“…Hence, the K + /Na + ratio is considered one of the main physiological strategies adopted by plants to resist salt stress (Singh et al 2019). Our results suggest that ion concentrations and high K + /Na + ratios may be useful selection indices for salt tolerance, consistent with the ndings of Genc et al (2010), Xu et al (2012), Masoudi et al (2015), and Ahmadi et al (2020). We observed that genotypes G5 and G20 showed the lowest SN and highest RK, SK, RKN, and SKN.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, the K + /Na + ratio is considered one of the main physiological strategies adopted by plants to resist salt stress (Singh et al 2019). Our results suggest that ion concentrations and high K + /Na + ratios may be useful selection indices for salt tolerance, consistent with the ndings of Genc et al (2010), Xu et al (2012), Masoudi et al (2015), and Ahmadi et al (2020). We observed that genotypes G5 and G20 showed the lowest SN and highest RK, SK, RKN, and SKN.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies revealed that fresh and dry weights of both roots and shoots of wheat seedlings were negatively affected by different levels of salinity (Athar et al 2007; Afzal et al 2008;Ghiyasi et al 2008;Akbarimoghaddam et al 2011). Reduction of photosynthetic processes and its related parameters under salinity conditions were also reported by Guo et al (2015), Zou et al (2016), and Ahmadi et al (2020).…”
Section: Introductionsupporting
confidence: 56%
“…However, some genotypes with the minimum reduction in growth and physiological features showed a relative ability to cope with salinity effects (Tables 2-4). Several studies reported similar results in barley and other crops (Tavakkoli et al 2010;Ahmadi et al 2018;Rajeswari et al 2019;Ahmadi et al 2020). The root system is the first plant organ that encounter directly in contact with the saline solutions in the soil and gets damage (Alam et al 2015;Rasel et al 2020).…”
Section: Discussionmentioning
confidence: 58%
“…It has been argued that AKT1 overexpression improves osmotic and stress tolerance by increasing tissue levels of K + ( Ahmad et al, 2016 ). With advances in molecular biology and biotechnology tools, the roles of TaHKT1;5 and TaSOS1 in Na + exclusion and its mechanisms have been exhaustively characterized in previous research ( Zhu et al, 2016a ; Wu et al, 2018 ; Ahmadi et al, 2020 ). However, there are few studies on TaAKT1 , and its mechanism in maintaining K + homeostasis under salt stress needs further research.…”
Section: Introductionmentioning
confidence: 99%